A study of polarization in MHD power generator - Chaturvedi N. (My University, 2025)
The effect of polarization and charge density on power flow efficiency and current have been studied in the Faraday type MHD generator. It has been found that polarization and charge density reduce the power density by a few percent. © 1990.